Análisis de la resolución de problemas de hidrostática en el bachillerato - Moreno MartÃnez, NehemÃas; Aguilar Tamayo, Manuel Francisco; Angulo Villanueva, Rita Guadalupe; RamÃrez Maciel, Juan Carlos (Revista Electrónica de Enseñanza de las Ciencias, 2019)
This research presents an analysis of the resolution of a physics problem that involves the phenomenon of body flotation. The resolution process carried out by a group of students and professors of high school is represented by the use of the technique of Hybrid Conceptual Maps and interpreted in the light of the Ontosemiotic Approach. It was observed that students develop models guided by perceptual and everyday concepts, regardless of the Newtonian theoretical reference and the realization of cognitive processes such as idealization, schematization, materialization, among others, which support the success of the resolution carried out by the teachers. The text describing the problem should follow a didactic strategy and not motivate the use of perceptual knowledge.